2021
DOI: 10.3389/fpubh.2021.659017
|View full text |Cite
|
Sign up to set email alerts
|

Processes for Implementing Community Health Worker Workforce Development Initiatives

Abstract: Introduction: The objective of this observational, cross-sectional study was to identify, document, and assess the progress made to date in implementing various processes involved in statewide community health worker (CHW) workforce development initiatives.Methods: From September 2017 to December 2020, we developed and applied a conceptual model of processes involved in implementing statewide CHW initiatives. One or more outputs were identified for each model process and assessed across the 50 states, D.C., an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Barbero et al developed a model to assess progress in developing CHW initiatives in all 50 states [ 9 ]. They identified 12 strategies being used to support CHW initiatives, such as involving CHWs in statewide health systems and supporting statewide CHW organizations.…”
Section: Resultsmentioning
confidence: 99%
“…Barbero et al developed a model to assess progress in developing CHW initiatives in all 50 states [ 9 ]. They identified 12 strategies being used to support CHW initiatives, such as involving CHWs in statewide health systems and supporting statewide CHW organizations.…”
Section: Resultsmentioning
confidence: 99%
“…State level assessments examining work and certification preferences of CHWs is a crucial step for the future growth of this workforce (CDC, 2019). A recent systematic literature review reported that 26 states have attempted to complete statewide assessments of their CHW workforce (Barbero et al., 2021); however there has been little research on the perspectives of CHWs concerning CHW certification, factors associated with certification preference, and qualitative feedback to substantiate these perspectives. In this study, CHWs from Nebraska overwhelmingly supported CHW certification (84% vs. 16%), which is similar to the few states that examined the certification preferences among CHWs, including Arizona in 2015 (Ingram et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Return-on-investment analysis has shown that CHWs can provide economic benefits and are a cost-effective way to connect patients with care. [23][24][25][26] Because of growing recognition of the contribution of CHWs in improving health and reducing costs, state Medicaid programs have increasingly developed reimbursement models that include this workforce.…”
Section: Medicaid Support Of Chwsmentioning
confidence: 99%
“…In addition to direct reimbursement for CHW services by some states, other states include CHW services in innovative Medicaid payment models. 24 Reimbursement through Medicaid could benefit CHWs and their clients, offering more sustainable support than time-limited grants or annual appropriations. However, any approach to CHW coverage and reimbursement could have substantial unintended effects on CHWs' practice.…”
Section: Medicaid Support Of Chwsmentioning
confidence: 99%
See 1 more Smart Citation